Step-by-Step Assembly of Self-Patterning Polyelectrolyte Films Violating (Almost) All Rules of Layer-by-Layer Deposition - Cini, Nejla; Tulun, Tülay; Decher, Gero; Ball, Vincent (American Chemical Society (ACS), 2010)
Because of its versatility, the layer-by-layer (LBL) assembly method has become a popular tool for preparing multimaterial films, yet astonishingly little is known about the fundamental rules governing their deposition. Here we show an unusual case of self-patterning LBL films made from poly(allylamine hydrochloride) and poly(sodium phosphate). In such films, both the film thickness and the film roughness increase linearly with the number of deposition steps up to a thickness of approximately 60 nm. Even more surprising is the fact that the adsorption of individual "layers" of polyanions and polycations proceeds without a regular inversion of the zeta potential and with the occurrence of a growth instability at approximately 75 layers. These findings underline the need to reconsider the fundamentals of polyelectrolyte multilayer film deposition.